2003
DOI: 10.1046/j.1471-4159.2003.01719.x
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of bradykinin and nitric oxide to AT2 receptor‐mediated differentiation in PC12 W cells

Abstract: We investigated the effect of angiotensin II on intracellular cyclic GMP content and neurite outgrowth as an indicator of cell differentiation in PC12 W cells. Neurite outgrowth was examined by phase-contrast microscopy. Outgrown neurites were classified as small, medium and large, and were expressed as neurites per 100 cells. Angiotensin II (10 )7 M) increased the outgrowth of medium and large neurites by mean ± SEM 20.2 ± 2.3 and 6.6 ± 1.4 compared with 1.66 ± 0.5 and 0.1 ± 0.06 neurites per 100 cells in con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 31 publications
4
23
1
Order By: Relevance
“…effect of activated AT 2 R on cGMP and NO production. 38 Both B 2 R agonist and antagonist were observed to have a similar influence on NO production when combined with AT 2 R agonist. However, the mechanism of NO production because of B 2 R agonist is different from that of the antagonist.…”
Section: Discussionmentioning
confidence: 93%
“…effect of activated AT 2 R on cGMP and NO production. 38 Both B 2 R agonist and antagonist were observed to have a similar influence on NO production when combined with AT 2 R agonist. However, the mechanism of NO production because of B 2 R agonist is different from that of the antagonist.…”
Section: Discussionmentioning
confidence: 93%
“…Accordingly, in the rat aorta, ANG increases cGMP levels by stimulation of bradykinin and subsequent NO production via AT 2 receptors [33] and, in hypertrophied rat hearts, blockade of AT 2 receptors results in reduced cGMP levels that augments the growth promoting effect of AT 1 receptor stimulation [34]. Recent data also suggest the participation of NO/cGMP-and bradykininpathways in AT 2 receptor-mediated PC12W cell differentiation and in the inhibition of ANG-induced contraction of rat uterine arteries by AT 2 receptors [35,36].…”
Section: At 2 Receptor Signal Transduction Pathwaysmentioning
confidence: 97%
“…In PC12 cells, it has been further shown that NO donors also enhanced the neuritogenic effects of NGF, however, NO donors did not induce PC12 cell neurites in the absence of NGF. 3,4) Meanwhile, we and other investigators have previously reported that several NO donors induced neurites in PC12h cells 5) and PC12W, 6) a subclone of PC12 cells, and in NG108-15. 7) NO plays an important role in intracellular and intercellular signaling events such as neural development, synaptic plasticity, and neuroendocrine secretion by low level NO production through neuronal and/or endothelial NOS activation.…”
Section: Introductionmentioning
confidence: 82%